Combination of Panax ginseng C. A. Mey and Febuxostat Boasted Cardioprotective Effects Against Doxorubicin-Induced Acute Cardiotoxicity in Rats - Al-Kuraishy, Hayder M.; Al-Hussaniy, Hany A.; Al-Gareeb, Ali I.; Negm, Walaa A.; El-Kadem, Aya H.; Batiha, Gaber El-Saber; N. Welson, Nermeen; Mostafa-Hedeab, Gomaa; Qasem, Ahmed H; Conte-Junior, Carlos Adam (Frontiers in Pharmacology, 2022)
Doxorubicin (DOX) is an anticancer agent for treating solid and soft tissue malignancies. However, the clinical use of DOX is restricted by cumulative, dose-dependent cardiotoxicity. Therefore, the present study aimed to assess the cardioprotective effects of Panax ginseng C.A.Mey, febuxostat, and their combination against DOX-induced cardiotoxicity. Thirty-five Sprague Dawley male rats were used in this study. The animals were randomly divided into five groups, with seven rats per group. The control group received normal saline, the induced group received DOX only, and the treated group received P. ginseng, febuxostat, and their combination before DOX treatment. Biomarkers of acute cardiac toxicity were assessed in each group. Results showed that treatment with the combination of febuxostat and P. ginseng before DOX led to a significant improvement in the biomarkers of acute DOX-induced cardiotoxicity. In conclusion, the combination of P. ginseng and febuxostat produced more significant cardioprotective effects against DOX-induced cardiotoxicity when compared to either P. ginseng or febuxostat when used alone. The potential mechanism of this combination was mainly mediated by the anti-inflammatory and antioxidant effects of P. ginseng and febuxostat.